The Social Work In Handling Terrorism: Roles And Challenges - Belgis Hayyinatun Nufus (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi Pancor, 2024)
Social work is a profession that has been doing social work which since the 20th century has expanded not only to social issues but also to terrorism. This article discussed the role of social worker in handling terrorism based on the international experiences and the challenges faced by social worker. The study was primarily based on the desk review of the credible and up to date literatures. There are few roles that can be done by social worker in handling terrorism such as being the community assessment and social brokerage, direct planner, direct implementation of team assistance, direct implementation of crisis services, support and assistance, assist in in community intervention, evaluator, expert, broker, mediator, counsellor, advocate, motivator, educator. Though there are few challenges faced by social worker in carrying out their role, there is also alternative solution that can be done to face this existing challenges. The experiences social worker had in several countries shows that this profession should be involved in handling terrorism.